Pengaruh Motivasi Kerja Terhadap Kinerja Karyawan pada Staff Office PT Summit Adyawinsa Indonesia - Fa’uzobihi Fa’uzobihi; Siti Nur Afifah; Partimah Partimah (CV. Ulil Albab Corp, 2024)
This Research is a quantitative research using questionnaires as a data collection tool distributed to respondents with a sample of 60 people. In analyzing the data, simple linear regression analysis and hypothesis testing were used. This study aims to determine how much influence work motivation has on employee performance in the office staff of PT Summit Adyawinsa Indonesia. Based on the results of the analysis carried out using SPSS 25.0, the value of Work Motivation (X) on Employee Performance (Y) can be explained by the regression formula Y= a+bX, then the regression value resulting from the calculayion above is Y= 20,726+0,616X. Based on the results of the t test, namely t count (5,803) is smaller than the t table value (2,000). Then work motivation has a high positive influence with an r value of (0,606) and has a contribution of 36,7% on Employee Performance of PT Summit Adyawinsa Indonesia (SAI). While the rest is influenced by other factors that were not included in the research.